Sesame cake fertilizer improves tobacco aroma quality by boosting root growth and leaf aroma precursor formation - Qi, Changyue; Lei, Jia; Ye, Weiguo; Zhang, Xi; Li, Zhouwen; Zhong, Xianyun; Tong, Dewen; Deng, Shiyuan; Chen, Jianjun; Wang, Yuanyuan (Frontiers in Plant Science, 2025)
Weak flavor in flue-cured tobacco compromises quality, making aroma enhancement crucial. Sesame cake fertilizer (SF) has the potential for improving tobacco aroma, but its effects on aroma components and mechanism remain unclear. Here, a four-year field experiment was conducted in Southern tobacco region of China to compare SF with conventional fertilization (CK). We investigated how SF influences soil quality, root and leaf development, aroma precursor accumulation, and volatile aroma composition to enhance tobacco aroma quality. Our results indicated that SF improved soil structure, pH, organic matter, and cation exchange capacity (CEC). It promoted root growth, dry matter accumulation, and root activity and CEC. Leaf photosynthesis and plastid pigment content increased due to enhanced chloroplast ultrastructure. SF also boosted glandular trichome density and secretion, leading to higher aroma precursor accumulation, particularly cembratriene-diol. After curing, 17 of 18 differential volatile aroma substances were upregulated, including carotenoids, cembratriendid alkyl degradation products, esters, terpenes, and heterocyclic compounds. Further, SF significantly increased sensory quality of flue-cured tobacco by promoting aroma quality and volume, and electronic nose analysis also confirmed this. Therefore, SF improves tobacco aroma by enhancing soil health, root growth, and leaf precursor formation. The “soil-root-leaf-differential aroma substances” framework highlights its role in increasing carotenoid and cembratriene-diol content, contributing to higher volatile aroma concentrations. This study highlights the potential of SF as a sustainable agricultural product for improving soil health and tobacco quality.